2019
DOI: 10.1021/acs.chemrestox.8b00281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silver Nanoparticle Exposure to the Testicular Antioxidant System during the Prepubertal Rat Stage

Abstract: Humans and environments are constantly exposed to a wide range of commercial products containing silver nanoparticles (AgNPs) in their composition. The hypothalamic-pituitary-testicular (HP-testicular) axis is sensitive to low doses of AgNPs with repercussions in sperm functionality. The oxidative stress may be related to the pathogenesis of sperm alterations because Ag+ ions are released from AgNPs in the corporal fluids. This study aimed to investigate the effects of AgNP exposure in the antioxidant defense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…AgNPs with different sizes and surface coatings or without coatings are likely to contribute to these different results. Lopes et al [38] reported that coated AgNPs have a better dispersion ability and are exposed to cells in a better way than non-coated AgNPs. In addition, the toxicity level varies among the type and origin of the cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…AgNPs with different sizes and surface coatings or without coatings are likely to contribute to these different results. Lopes et al [38] reported that coated AgNPs have a better dispersion ability and are exposed to cells in a better way than non-coated AgNPs. In addition, the toxicity level varies among the type and origin of the cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…AgNPs with different sizes and surface coatings or without coatings are likely to contribute to these different results. Lopes et al [43] reported that coating-AgNPs had a better dispersion than AgNPs and was more fully exposed to the cells. When compared to L02 cells, HepG2 cells are more sensitive to AgNPs at the exposure level of 20-160 μg/mL [44].…”
Section: Discussionmentioning
confidence: 99%
“…A histological study has also shown that graphene oxide exposure was associated with structural damage in the testis, which included atrophy of seminiferous tubules with a reduction in germinal epithelium, germ cell loss, and vacuolization (Nirmal et al 2017). It was reported that male rats exposed to silver nanoparticles (AgNPs) induced alterations in the testis seminiferous tubule morphometry (Lopes et al 2019). Cerium oxide nanoparticles (CeO 2 NPs) revealed congestion and degeneration of seminiferous tubules and decreased sperm motility and count and increased total sperm abnormality in mice (Adebayo et al 2018).…”
Section: Nontoxic Effects In Male Germ Cellsmentioning
confidence: 99%